2011
DOI: 10.3389/fmicb.2011.00213
|View full text |Cite
|
Sign up to set email alerts
|

Re-Examining the Role of Hydrogen Peroxide in Bacteriostatic and Bactericidal Activities of Honey

Abstract: The aim of this study was to critically analyze the effects of hydrogen peroxide on growth and survival of bacterial cells in order to prove or disprove its purported role as a main component responsible for the antibacterial activity of honey. Using the sensitive peroxide/peroxidase assay, broth microdilution assay and DNA degradation assays, the quantitative relationships between the content of H2O2 and honey’s antibacterial activity was established. The results showed that: (A) the average H2O2 content in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
142
2
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(175 citation statements)
references
References 39 publications
4
142
2
8
Order By: Relevance
“…Black locust (n = 7), chestnut (n = 3), lime (n = 5), honeydew (n = 12) and mint (n = 3) honeys were diluted by deionized water at five different mass to volume ratios (1:1; 1:2; 1:4; 1:8; 1:16) and after 60 minutes of incubation at 37 °C, the content of the produced hydrogen peroxide was measured by the MQuant peroxide test strips. However, since hydrogen peroxide formation in honey depends on the glucose oxidase (GOX) action (Brudzynski 2006;Brudzynski et al, 2011;Kerkvliet, 1996), it was necessary to determine the activity of this enzyme in honey samples before measuring the hydrogen peroxide content in honey solutions. Determination of GOX in honey samples by the standard horseradish peroxidase/o-dianisidin method revealed that all examined samples possessed the glucose oxidase activity, and can thus be analysed for hydrogen peroxide accumulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Black locust (n = 7), chestnut (n = 3), lime (n = 5), honeydew (n = 12) and mint (n = 3) honeys were diluted by deionized water at five different mass to volume ratios (1:1; 1:2; 1:4; 1:8; 1:16) and after 60 minutes of incubation at 37 °C, the content of the produced hydrogen peroxide was measured by the MQuant peroxide test strips. However, since hydrogen peroxide formation in honey depends on the glucose oxidase (GOX) action (Brudzynski 2006;Brudzynski et al, 2011;Kerkvliet, 1996), it was necessary to determine the activity of this enzyme in honey samples before measuring the hydrogen peroxide content in honey solutions. Determination of GOX in honey samples by the standard horseradish peroxidase/o-dianisidin method revealed that all examined samples possessed the glucose oxidase activity, and can thus be analysed for hydrogen peroxide accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…Such slight changes in pH upon honey dilution were not surprising, since it is well known that honey acts as a buffer (Buba et al, 2013). (Brudzynski, 2006;Brudzynski et al, 2011;Brudzynski et al, 2017), by measurement of oxygen concentration (decomposition of H 2 O 2 by exogenously added catalase) (Bang et al, 2004), while only Cooke et al (2015) measured hydrogen peroxide content in honeys using MQuant test strips, but examined special types of honey. According to our knowledge, there is only one other report on the H 2 O 2 content in honeys where MQuant test strips were used (Kerkvliet, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…In several studies, it has been shown that hydrogen peroxide was the main compound responsible for the antibacterial action of honey (Brudzynski, 2006;Weston, 2000;White Jr, 1963) and was produced mainly during glucose oxidation, which is catalyzed by the bee enzyme glucose oxidase (White Jr, 1963). If a honey contains a high content of this oxidizing compound, bacteria cannot respond normally to proliferative signals, and their growth remains arrested even when the honey is used in diluted forms (Brudzynski, 2011). According to Kretavičius et al (2010), when honey was liquefied, glucose oxidase was activated and produces its metabolic products.…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
“…The presence of hydrogen peroxide generated by enzymatic activity of glucose oxidase in diluted honey is considered as the major antibacterial factor [11]. Furthermore, heating honey inactivates the glucose and it oxidates phenolic compounds as important factors for the non-peroxide antibacterial activity of honey [10]. The non-peroxide antibacterial activity is insensitive to heat and light [12].…”
Section: Introductionmentioning
confidence: 99%
“…Several bioactive compounds have been identified in honey which contributed to its antibacterial action. In many studies, the presences of peroxide and non-peroxide antibacterial capacity in honey have been reported [9,10]. The presence of hydrogen peroxide generated by enzymatic activity of glucose oxidase in diluted honey is considered as the major antibacterial factor [11].…”
Section: Introductionmentioning
confidence: 99%